2021
DOI: 10.1186/s40462-021-00267-5
|View full text |Cite|
|
Sign up to set email alerts
|

Far eastern curlew and whimbrel prefer flying low - wind support and good visibility appear only secondary factors in determining migratory flight altitude

Abstract: Background In-flight conditions are hypothesized to influence the timing and success of long-distance migration. Wind assistance and thermal uplift are thought to reduce the energetic costs of flight, humidity, air pressure and temperature may affect the migrants’ water balance, and clouds may impede navigation. Recent advances in animal-borne long-distance tracking enable evaluating the importance of these factors in determining animals’ flight altitude. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…We found significantly higher flight altitudes during spring compared with autumn, in accordance with the observation of flight altitudes in the vicinity of curlew wintering sites at the Wadden Sea, which were related to different wind regimes (Schwemmer et al, 2021). Galtbalt et al (2021) found median flight altitudes of 538 m over land and 156 m over sea for Far Eastern curlews Numenius madagascariensis during north-bound migration. Interestingly, this was similar to the range for spring migration in our study, while our study showed significantly lower flight altitudes during autumn.…”
supporting
confidence: 89%
“…We found significantly higher flight altitudes during spring compared with autumn, in accordance with the observation of flight altitudes in the vicinity of curlew wintering sites at the Wadden Sea, which were related to different wind regimes (Schwemmer et al, 2021). Galtbalt et al (2021) found median flight altitudes of 538 m over land and 156 m over sea for Far Eastern curlews Numenius madagascariensis during north-bound migration. Interestingly, this was similar to the range for spring migration in our study, while our study showed significantly lower flight altitudes during autumn.…”
supporting
confidence: 89%
“…What our two scenarios have in common is that work during the climb is not wasted but invested in (and to a large degree recoverable from) the potential energy gained ( Pennycuick, 1969 ). We therefore urge caution when using ‘climbing costs’ per se as an explanation for low-altitudinal flights if these costs are not well formulated, as it may be misleading and could obscure the effect of other undefined factors ( Galtbalt et al, 2021 ). We hope our approach will inspire further analyses of the potential penalty of vertical movements and encourages researchers in attempting to enumerate such costs in future flight altitude-related studies.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we broaden this definition to also include any larger to-and-fro movements when the bird is airborne at any stage of the migratory flight. Only focusing on the increased power output during climbing may lead to the assumption that extensive vertical movements would elevate the cost of migration and limit the possible benefits of a tailwind at higher altitudes ( Galtbalt et al, 2021 ). But, because of the potential energy gained during ascents, migrants are expected to preserve energy through gliding descents ( Baudinette and Schmidt-Nielsen, 1974 ), which in ideal circumstances could completely balance the climbing costs.…”
Section: Introductionmentioning
confidence: 99%
“…We found that godwits generally appeared to seek out favorable wind conditions in their preferred direction within a limited vertical column extending from 100 to 3000 m.a.s.l. This often entailed low-level flights over the Pacific Ocean, a strategy that has been documented in other shorebirds making transoceanic crossings [ 56 ], as well as dynamic altitude-switching, which may incur lower costs for nimble, long-winged godwits than for other larger-bodied species [ 57 ]. Other factors not included in our models, such as predation risk or thermoregulation, may have also influenced flight altitude [ 58 , 59 ], though our models suggest that their effects are likely minimal over much of this flight.…”
Section: Discussionmentioning
confidence: 99%